Lidar Soundings of Noctilucent Clouds during the PMC Turbo Balloon Mission - Kaifler, Natalie; Kaifler, Bernd; Rapp, Markus; Fritts, D. C.; Williams, Bifford P.; Kjellstrand, Bjorn; Geach, Christopher; Miller, Amber; Limon, Michele; Hanany, Shaul; Jones, Glenn; Reimuller, Jason (2019)
Noctilucent clouds are optically thin layers of ice particles occuring around 83 km altitude during polar summer. Their intriguing fine-scale structure provides a means to study atmospheric waves and instabilities in the sensitive mesopause region of our atmosphere. For the first time, noctilucent clouds were observed using a backscatter lidar and multiple cameras from a balloon platform. The NASA long-duration balloon PMC-Turbo was launched in July 2018 from Kiruna, Sweden, and floated at 40 km altitude during six days to northern Canada. During the mission, a large dataset with unprecedented high-resolution soundings of noctilucent clouds down to scales of few meters were obtained. The combination of near-vertical lidar soundings with horizontal structures visible in narrow- and wide-field of view cameras allows to fully characterize the morphological structures of noctilucent clouds that are modulated by gravity waves, and reveal dynamic processes such as the breaking of these waves, the generation of various types of instabilities and transitions to turbulence.